Fire-resistant anti-oxidation coating for carbon-based composite material, preparation method of fire-resistant anti-oxidation coating and preparation method of fire-resistant anti-oxidation coating on carbon-based composite material

Through the combination of oxides such as SiO2, Al2O3 and phosphoric acid and alkaline silica sol, the problems of high-temperature oxidation and insufficient coating performance of carbon-based composite materials are solved, and efficient and simple coating preparation is achieved, providing excellent anti-oxidation and thermal shock resistance, suitable for high-temperature brake discs.

CN119263887APending Publication Date: 2025-01-07HONGDE NEW MATERIAL TECH (HULUDAO) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411453079.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Carbon-based composite materials are prone to oxidation at high temperatures, resulting in reduced strength and shortened service life. The existing coatings have defects in wet performance, thickness uniformity, oxidation resistance and thermal shock resistance, and the preparation process is cumbersome.

Method used

Refractory antioxidant coating composed of a mixture of SiO2, Al2O3, B4C, Y2O3, ZnO, Zn3(PO4)2, Mg3(PO4)2, Al(PO3)3, phosphoric acid solution and alkaline silica sol, is grinding, stirring and The coating slurry is uniformly added to form, applied to the carbon-based composite material and baked at high temperatures to form a refractory and antioxidant coating.

Benefits of technology

It realizes uniform and dense coating, strong bonding with the substrate, excellent thermal shock resistance, reduces preparation cost and process complexity, enhances the water resistance and oxidation resistance of the coating, and meets the use needs of high-temperature brake discs such as aircraft. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263887A_ABST
    Figure CN119263887A_ABST
Patent Text Reader

Abstract

The invention discloses a fire-resistant anti-oxidation coating for a carbon-based composite material, a preparation method of the fire-resistant anti-oxidation coating and a preparation method of a fire-resistant anti-oxidation coating on the carbon-based composite material, and relates to the technical field of anti-oxidation coatings. The prepared coating is uniform and compact, good in binding force with a matrix and excellent in thermal shock resistance. After 100 times of brake tests with different energies, all the carbon brake discs are complete in structure, the anti-oxidation coating on the non-friction surface does not fall off, and the friction ring does not have an oxidation sign. The coating is good in wettability with a base material and excellent in thermal shock resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-oxidation coatings, and in particular to a fire-resistant anti-oxidation coating for carbon-based composite materials, a preparation method thereof, and a preparation method of the fire-resistant anti-oxidation coating on the carbon-based composite material. Background Art

[0002] Carbon-based composite materials (including C / C, C / C-SiC) have the advantages of low density, high high-temperature strength, large specific heat capacity, and excellent friction and wear performance, and are widely used in friction materials under various working conditions. However, since carbon-based composite materials contain carbon fiber and pyrolytic carbon, they will oxidize in the air at around 370°C, which will affect the strength of the material and shorten its service life.

[0003] The carbon-based composite materials used for aircraft braking have a heat storage volume temperature of 450-750℃ during normal braking, and 550-850℃ during high-energy braking. Due to the high braking frequency of aircraft brake discs, as aircraft brake materials, in addition to requiring the coating to have certain anti-oxidation properties, it is also required to have high thermal shock resistance. Carbon-based composite brake disc products usually use two types of boron coatings and phosphorus coatings. The former generally has the disadvantages of insufficient wet performance, poor thermal shock resistance, and poor coating uniformity, while the latter has the problem of insufficient antioxidant performance above 700℃. Generally, the anti-oxidation coating consists of at least two layers, and each time it requires the application, drying and heat treatment steps, and the process is relatively cumbersome. Therefore, it is very important to prepare a coating with a simple method, excellent water resistance, antioxidant properties, and thermal shock resistance. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a fire-resistant and anti-oxidation coating for carbon-based composite materials, a preparation method thereof, and a preparation method of a fire-resistant and anti-oxidation coating on a carbon-based composite material. The coating has good bonding strength and better performance, and solves the problems of insufficient wet performance, uneven thickness, insufficient anti-oxidation performance, and poor thermal shock resistance of existing coatings. The preparation method is simple, low-cost, and easy to maintain.

[0005] In the first aspect, the present invention provides a fire-resistant and antioxidant coating for carbon-based composite materials, comprising the following components: a mixture of SiO2, Al2O3, B4C, Y2O3, ZnO, Zn3(PO4)2, Mg3(PO4)2, Al(PO3)3, a phosphoric acid solution and an alkaline silica sol.

[0006] Furthermore, the proportion of each component in the mixture is: 10-15wt.% SiO2 powder, 20-25wt.% Al2O3 powder, 5-10wt.% B4C powder, 5-10wt.% Y2O3 powder, 10-15wt.% ZnO, 10-15wt.% Zn3(PO4)2 powder, 10-15wt.% Mg3(PO4)2 powder, and 10-15wt.% Al(PO3)3 powder.

[0007] Furthermore, 2-5 times the weight of the mixture powder is added with phosphoric acid, the concentration of the phosphoric acid solution is 20-25wt.%; 2-4 times the weight of the mixture powder is added with alkaline silica sol, the model of the alkaline silica sol is AR-830.

[0008] The coating provided by the present invention has a high degree of adhesion to the substrate, is not easy to fall off, has good wettability, and has excellent thermal shock resistance.

[0009] In a second aspect, the present invention provides a method for preparing a fire-resistant and anti-oxidation coating for a carbon-based composite material, the steps being as follows:

[0010] Put SiO2, Al2O3, B4C, Y2O3, ZnO, Zn3(PO4)2, Mg3(PO4)2 and Al(PO3)3 into an agate mortar and grind and mix them thoroughly according to the matching ratio to obtain a mixed powder;

[0011] Add phosphoric acid solution dropwise to the mixed powder, and then stir thoroughly to prepare a primary slurry;

[0012] Finally, alkaline silica sol is added to the primary slurry, the viscosity is controlled to be 4-20 mPa·s and stirred evenly to obtain a coating slurry.

[0013] Furthermore, the proportion of each component in the mixed powder is: 10-15wt.% SiO2 powder, 20-25wt.% Al2O3 powder, 5-10wt.% B4C powder, 5-10wt.% Y2O3 powder, 10-15wt.% ZnO, 10-15wt.% Zn3(PO4)2 powder, 10-15wt.% Mg3(PO4)2 powder, and 10-15wt.% Al(PO3)3 powder.

[0014] Furthermore, the concentration of the phosphoric acid solution is 20-25 wt.%, and the amount used is 2-5 times the total weight of the mixed powder.

[0015] Furthermore, the alkaline silica sol model is 830 silica sol, and its usage is 2 to 4 times of the total weight of the mixed powder.

[0016] The preparation method of the coating is simple, conventional operating environment can be met, and the production cost is low.

[0017] In a third aspect, the present invention provides a method for preparing a fire-resistant and anti-oxidation coating on a carbon-based composite material, comprising the following steps:

[0018] The fire-resistant and anti-oxidation coating for carbon-based composite materials is evenly applied on the non-friction surface of the carbon-based composite materials, and the coating thickness is controlled to be 0.01 to 0.03 mm;

[0019] The coated carbon-based composite material is placed in an oven and dried until the surface is dry and has no glossiness;

[0020] The dried carbon-based composite material is placed at high temperature, in a nitrogen protective atmosphere, and heated to 750-950°C at a heating rate of 5°C / min, kept warm for 1-2 hours, and then taken out after freely cooling to room temperature, to form a fire-resistant and oxidation-resistant coating on the carbon-based composite material.

[0021] Furthermore, the temperature in the oven is 120° C., and the drying time is 2 to 4 hours.

[0022] Compared with the existing coating preparation method, the coating preparation method of the present invention is simpler to operate, convenient for on-site maintenance, and has a high controllability of coating thickness.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The coating prepared by the present invention is uniform and dense, has good bonding strength with the substrate, and has excellent thermal shock resistance. After 100 braking tests with different energies, all carbon brake discs have intact structures, the anti-oxidation coating on the non-friction surface has not fallen off, and the friction ring has no signs of oxidation. The coating has good wettability with the substrate material and has excellent thermal shock resistance.

[0025] (2) The preparation method of the present invention is simple, low in cost, and convenient for on-site maintenance. Generally, the anti-oxidation coating consists of at least two layers, and each layer requires application, drying and heat treatment steps, which is a relatively complicated process. The coating of the present invention only needs to be applied 2-3 times and is relatively thin.

[0026] (3) The coating prepared by the present invention has good water resistance and excellent antioxidant properties, and can be used in batches on the non-friction surface of carbon-based composite brake discs or clutch discs of aircraft / high-speed railways / armored vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the cross-sectional morphology of the brake disc after constant temperature oxidation at 800℃ for 50h in the coating test.

[0028] Figure 2 This is a photo of the coating before bench testing.

[0029] Figure 3 This is a photo of the coating after bench testing. DETAILED DESCRIPTION

[0030] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific implementation methods, but the present invention is not limited thereto.

[0031] Preparation Example 1 of coating

[0032] According to the formula ratio, 10wt.% SiO2 powder, 20wt.% Al2O3 powder, 10wt.% B4C powder, 5wt.% Y2O3 powder, 10wt.% ZnO, 15wt.% Zn3(PO4)2 powder, 15wt.% Mg3(PO4)2 powder, and 15wt.% Al(PO3)3 powder were weighed and put into an agate mortar and fully ground and mixed for 60 minutes to obtain a mixed powder; 20wt.% phosphoric acid solution was dripped into the mixed powder, and the amount of phosphoric acid solution was 4 times the total mass of the mixed powder. After that, a magnetic stirrer was used for 30 minutes to prepare a primary slurry with a certain viscosity; finally, alkaline silica sol (AR-830, purchased product) 4 times the weight of the powder was added to the slurry, the viscosity was controlled at 10mPa·s, and stirred evenly to obtain a ceramic coating slurry.

[0033] Preparation Example 2 of coating

[0034] According to the formula ratio, 15wt.% SiO2 powder, 25wt.% Al2O3 powder, 10wt.% B4C powder, 10wt.% Y2O3 powder, 10wt.% ZnO, 10wt.% Zn3(PO4)2 powder, 10wt.% Mg3(PO4)2 powder, and 10wt.% Al(PO3)3 powder were weighed and put into an agate mortar and fully ground and mixed for 30 to 60 minutes to obtain a mixed powder; 25wt.% phosphoric acid solution was dripped into the mixed powder, and the amount of phosphoric acid solution was 3 times the total mass of the mixed powder. Then, a magnetic stirrer was used for 30 minutes to prepare a primary slurry with a certain viscosity; finally, 5 times the weight of the powder was added to the slurry. Alkaline silica sol (AR-830) was added to the slurry, the viscosity was controlled at 20mPa·s, and it was stirred evenly to obtain a ceramic coating slurry.

[0035] Preparation Example 3 of coating

[0036] According to the formula ratio, 12wt.% SiO2 powder, 22wt.% Al2O3 powder, 10wt.% B4C powder, 10wt.% Y2O3 powder, 10wt.% ZnO, 12wt.% Zn3(PO4)2 powder, 12wt.% Mg3(PO4)2 powder, and 12wt.% Al(PO3)3 powder were weighed and put into an agate mortar for thorough grinding and mixing for 30 to 60 minutes to obtain a mixed powder; 25wt.% phosphoric acid solution was dripped into the mixed powder, and the amount of phosphoric acid solution was 3 times the total mass of the mixed powder. After that, a magnetic stirrer was used for 30 minutes to prepare a primary slurry with a certain viscosity; finally, alkaline silica sol (AR-830) 4 times the weight of the powder was added to the slurry, the viscosity was controlled at 8mPa·s, and stirred evenly to obtain a ceramic coating slurry.

[0037] Preparation of coating Comparative Example 1

[0038] Compared with the embodiment, no Y2O3 powder is added in the formula. Others are the same as the embodiment.

[0039] Preparation of coating Comparative Example 2

[0040] Compared with the example, no Mg3(PO4)2 powder is added in the formula. Others are the same as the example.

[0041] Example of preparing water-resistant and anti-oxidation coating on carbon-based brake disc

[0042] Sample processing: The carbon-based brake disc was ultrasonically cleaned and dried at 120°C.

[0043] Brushing: Use a soft-bristled brush to dip the prepared coating slurry and evenly apply it on the non-friction surface of the carbon disc. The coating thickness should be controlled at 0.02-0.04mm.

[0044] Drying: Place the carbon disc in a 120℃ oven and dry it for 2 to 4 hours until the surface is dry and glossy, and avoid the generation of bubbles.

[0045] Heat treatment: The dried carbon disc is placed in a nitrogen protective atmosphere at a high temperature, and the temperature is raised to 750-950°C at a rate of 5°C / min, and kept at this temperature for 2 hours. After the temperature drops to room temperature, it is taken out to form a water-resistant and anti-oxidation coating on the carbon-based brake disc.

[0046] Comparative Example 1 for Preparation of Water-Resistant and Anti-Oxidation Coating on Carbon-Based Brake Disc

[0047] A carbon-based brake disc coating was obtained by using the coating of Comparative Example 1 according to the method of Coating Preparation Example 3.

[0048] Comparative Example 2 for Preparation of Water-Resistant and Anti-Oxidation Coating on Carbon-Based Brake Disc

[0049] A carbon-based brake disc coating was obtained by using the coating of Comparative Example 2 according to the method of Coating Preparation Example 3.

[0050] The obtained coating samples and 1:1 carbon brake disc were subjected to performance tests, as follows:

[0051] (1) Constant temperature oxidation test

[0052] According to GJB 8181-2015 "Specifications for Carbon Brake Discs for Aircraft Wheels", after the coating samples were treated with an anti-oxidation coating, a high-temperature oxidation test was performed on the coating samples at 800°C in a tube furnace for 50 hours to measure their weight loss rate. Ten groups of parallel tests were performed on each sample to obtain the average value. The specific test data are shown in Table 1. At the same time, a scanning electron microscope (SEM) was used to observe the cross section of the sample after 50 hours of oxidation. Figure 1 As shown. As can be seen from the figure, the coating and the substrate are still closely bonded, indicating that high-temperature oxidation has no significant effect on the bonding performance between the coating and the substrate. Compared with Comparative Example 1, the embodiment adds Y2O3, which effectively improves the compactness and bonding strength of the coating. Compared with Comparative Example 2, the embodiment adds Mg3(PO4)2, which increases the content of magnesium phosphate and P2O5 with self-healing function at high temperatures. Various phosphates are prone to polymerization reactions at high temperatures to form more stable chain molecules, which are beneficial to the surface protection of the surface of carbon-based composite materials.

[0053] Table 1 Coating sample 800℃ constant temperature oxidation data

[0054]

[0055] (2) Thermal shock test

[0056] Referring to GJB 8181-2015 "Specifications for Carbon Brake Discs for Aircraft Wheels", after the coating samples (coating examples, coating comparative examples 1 and 2) were treated with anti-oxidation coating, a thermal shock test was performed on the coating samples using a tubular furnace, and the conditions were 800°C to room temperature, 50 cycles; 1000°C to room temperature, 30 cycles; 1200°C to room temperature, 5 cycles. In the above tests, each temperature section was immersed in water once, and its weight loss rate was measured. Three parallel tests were performed on each sample to take the average value, and the specific test data are shown in Table 2.

[0057] Table 2 Thermal shock test data of coating samples

[0058]

[0059] (3) Bench test

[0060] The coated X-type aircraft carbon brake disc was tested on a 1:1 bench at the Guilin Shuguang Rubber Research Institute. The braking items were divided into three categories: normal landing, overload landing and aborted takeoff. After a total of 105 braking tests, including 98 normal landings, 2 overload landings, and the number of aborted takeoff (RTO) braking increased from 1 to 5 times, the anti-oxidation coating was checked to have no shedding phenomenon, and the substrate was not oxidized, meeting the performance requirements. The disc before and after the test is as follows Figure 2 and Figure 3 As shown, no changes can be observed on the brake disc surface before and after the test.

[0061] Finally, it should be noted that the above are only preferred embodiments of the present invention. Of course, those skilled in the art can make changes and modifications to the present invention. If these modifications and variations fall within the scope of the claims of the present invention and their equivalent technologies, they should be considered to be within the scope of protection of the present invention.

Claims

1. A fire-resistant and anti-oxidation coating for carbon-based composite materials, characterized in that: The components include: A mixture of SiO2, Al2O3, B4C, Y2O3, ZnO, Zn3(PO4)2, Mg3(PO4)2, Al(PO3)3, phosphoric acid solution and alkaline silica sol.

2. The fire-resistant and anti-oxidation coating for carbon-based composite materials according to claim 1, characterized in that: The proportion of each component in the mixture is: 10~15wt.% SiO2 powder, 20~25wt.% Al2O3 powder, 5~10wt.% B4C powder, 5~10wt.% Y2O3 powder, 10~15wt.% ZnO, 10~15wt.% Zn3(PO4)2 powder, 10~15wt.% Mg3(PO4)2 powder, 10~15wt.% Al(PO3)3 powder.

3. The fire-resistant and anti-oxidation coating for carbon-based composite materials according to claim 1, characterized in that: Add 2-5 times the weight of phosphoric acid to the mixed powder, and add 2-4 times the weight of alkaline silica sol to the mixed powder. The alkaline silica sol model is 830 silica sol.

4. A method for preparing a fire-resistant and anti-oxidation coating for a carbon-based composite material, characterized in that: Here are the steps: Put SiO2, Al2O3, B4C, Y2O3, ZnO, Zn3(PO4)2, Mg3(PO4)2 and Al(PO3)3 into an agate mortar and grind and mix them thoroughly according to the matching ratio to obtain a mixed powder; Add phosphoric acid solution dropwise to the mixed powder, and then stir thoroughly to prepare a primary slurry; Finally, alkaline silica sol is added to the primary slurry, the viscosity is controlled at 4-20 mPa·s and stirred evenly to obtain a coating slurry.

5. The method for preparing a fire-resistant and anti-oxidation coating for carbon-based composite materials according to claim 4, characterized in that: The proportion of each component in the mixed powder is: 10~15wt.% SiO2 powder, 20~25wt.% Al2O3 powder, 5~10wt.% B4C powder, 5~10wt.% Y2O3 powder, 10~15wt.% ZnO, 10~15wt.% Zn3(PO4)2 powder, 10~15wt.% Mg3(PO4)2 powder, 10~15wt.% Al(PO3)3 powder.

6. The method for preparing a fire-resistant and anti-oxidation coating for carbon-based composite materials according to claim 4, characterized in that: The concentration of the phosphoric acid solution is 20-25wt.%, and the amount used is 2-5 times the total weight of the mixed powder.

7. The method for preparing a fire-resistant and anti-oxidation coating for carbon-based composite materials according to claim 4, characterized in that: The model of alkaline silica sol is 830 silica sol, and its usage is 2 to 4 times of the total weight of the mixed powder.

8. A method for preparing a fire-resistant and oxidation-resistant coating on a carbon-based composite material, characterized in that: The steps include: The fire-resistant and anti-oxidation coating for carbon-based composite materials according to any one of claims 1 to 3 is evenly applied on the non-friction surface of the carbon-based composite material, and the coating thickness is controlled to be 0.01 to 0.03 mm; The coated carbon-based composite material is placed in an oven and dried until the surface is dry and has no glossiness; The dried carbon-based composite material is placed at high temperature, in a nitrogen protective atmosphere, and heated to 750-950°C at a heating rate of 5°C / min, kept warm for 1-2 hours, and then taken out after freely cooling to room temperature, to form a fire-resistant and oxidation-resistant coating on the carbon-based composite material.

9. The method for preparing a fire-resistant and anti-oxidation coating on a carbon-based composite material according to claim 8, characterized in that: The temperature in the oven is 120°C and the drying time is 2 to 4 hours.

Citation Information

Patent Citations

  • Preparation method of low-temperature long-time oxidation-resistant coating layer on carbon / carbon composite material surfaces

    CN105646007A

  • Modified antioxidant composite phosphate coating as well as preparation method and application thereof

    CN113683429A

  • Aircraft carbon / carbon composite material brake disc repairing method and used adhesive

    CN115403400A

  • Carbon aerogel composite material surface wide-temperature-range anti-oxidation coating and normal-temperature preparation method

    CN118405942A

  • Process for protecting products made of composite material containing carbon against oxidation, and products obtained by the said process

    US5725955A